Cessation of Cigarette Smoking and the Impact on Cancer Incidence in Human Immunodeficiency Virus–infected Persons: The Data Collection on Adverse Events of Anti-HIV Drugs Study. (14th June 2018) - Shepherd, Leah; Ryom, Lene; Law, Matthew; Petoumenos, Kathy; Hatleberg, Camilla Ingrid; d'Arminio Monforte, Antonella; Sabin, Caroline; Bower, Mark; Bonnet, Fabrice; Reiss, Peter; de Wit, Stephane; Pradier, Christian; et al.
Abstract : This study of 35442 HIV-infected people found that the incidence of lung cancer was 10-fold higher 5 years after smoking cessation compared with never smokers; the incidence of other smoking-related cancers returned to levels of nonsmokers 2–3 years after smoking cessation. Abstract: Background: Cancers are a major source of morbidity and mortality for human immunodeficiency virus (HIV)–infected persons, but the clinical benefits of smoking cessation are unknown. Methods: Participants were followed from 1 January 2004 until first cancer diagnosis, death, or 1 February 2016. Smoking status was defined as ex-smoker, current smoker, and never smoker. Adjusted incidence rate ratios (aIRRs) were calculated using Poisson regression, adjusting for demographic and clinical factors. Results: In total 35442 persons from the Data Collection on Adverse Events of Anti-HIV Drugs (D:A:D) study contributed 309803 person-years of follow-up. At baseline, 49% were current smokers, 21% were ex-smokers, and 30% had never smoked. Incidence of all cancers combined (n = 2183) was highest <1 year after smoking cessation compared to never smokers (aIRR, 1.66 [95% confidence interval CI, 1.37–2.02]) and not significantly different from never smokers 1–1.9 years after cessation. Lung cancer incidence (n = 271) was elevated <1 year after cessation (aIRR, 19.08 [95% CI, 8.10–44.95]) and remained 8-fold higher 5 years after smoking cessation (aIRR, 8.69 [95% CI, 3.40–22.18]). Incidence of other smoking-related cancers (n = 622) was elevated in the first year after cessation (aIRR, 2.06 [95% CI, 1.42–2.99]) and declined to a level similar to nonsmokers thereafter. Conclusions: Lung cancer incidence in HIV-infected individuals remained elevated >5 years after smoking cessation. Deterring uptake of smoking and smoking cessation efforts should be prioritised to reduce future cancer risk.